Hedgehog pathway activation through nanobody-mediated conformational blockade of the Patched sterol conduit - Zhang, Yunxiao (Proc Natl Acad Sci U S A, 2020)
Activation of the Hedgehog pathway may have therapeutic value for improved bone healing, taste receptor cell regeneration, and alleviation of colitis or other conditions. Systemic pathway activation, however, may be detrimental, and agents amenable to tissue targeting for therapeutic application have been lacking. We have developed an agonist, a conformation-specific nanobody against the Hedgehog receptor Patched1 (PTCH1). This nanobody potently activates the Hedgehog pathway in vitro and in vivo by stabilizing an alternative conformation of a Patched1 “switch helix,” as revealed by our cryogenic electron microscopy structure. Nanobody-binding likely traps Patched in one stage of its transport cycle, thus preventing substrate movement through the Patched1 sterol conduit. Unlike the native Hedgehog ligand, this nanobody does not require lipid modifications for its activity, facilitating mechanistic studies of Hedgehog pathway activation and the engineering of pathway activating agents for therapeutic use. Our conformation-selective nanobody approach may be generally applicable to the study of other PTCH1 homologs.